The Influence of QRIS Service Costs on Technology Adoption and Micro, Small and Medium-sized Enterprises Performance - Midsurnight, Richie Bagus; An'im Kafabih (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
This study aims to analyze the factors that can influence SMEs in adopting QRIS payment system technology and the influence of technology adoption on SMEs' performance. This study uses the UTAUT theory as a fundamental theory in knowing the factor factors of technology adoption in SMEs, which is expanded as a theoretical framework in which fee value is added as a construction of UTAUT. Using SME's performance variable as a dependent variable to determine the impact of adopting a QRIS pay system technology. The study uses a quantitative approach to analyze the adoption technology of QRIS and the performance of SMEs. The analytical tool used is SEM-PLS with SmartPLS as an application to explain the research model. One hundred four respondents were selected through probability sampling. The research results showed that the entire construction of the variables UTAUT (Performance expectancy, effort expected, social influence, facilitating condition) and fee value positively and significantly influenced the adoption of QRIS payment system technology. Moreover, adopting QRIS payment system technology positively and significantly impacts SME performance in Semarang City.